Kinofikacija umetnosti - Gruber, Klemens (Slavistična revija, 2017)
"Cinematization" is a key concept of the 1920s. The new potential of film encouraged the drama to begin employing theatrical means to create filmic effects and to seek new staging formats and means more in line with public perceptions transformed by film. Nor were the other arts immune (literature, painting, photography, book making). Ultimately it is a matter of film's potential for representing a collectively experienced world.
Keywords: art; Eisenstein, Sergej, 1920-1991; film; gledališče; Gropius, Walter, 1883-1941; kinofikacija; Lissitzky, El, 1890-1941; Mejerhol'd, Vsevolod Emil'evič, 1874-1940; projekcijska platna; theater; umetnost